2000
DOI: 10.4049/jimmunol.164.3.1399
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Specific Targets for Regulation of IFN-γ Expression: Lamina Propria T Cells Use Differentcis-Elements than Peripheral Blood T Cells to Regulate Transactivation of IFN-γ Expression

Abstract: Activation of lamina propria (LP) T cells via the CD2 pathway enhances IFN-γ (IFN-γ) secretion with further enhancement after CD28 coligation. The molecular mechanisms regulating IFN-γ expression in LP T cells remain unknown. Previous studies in PBL and T cell lines identified cis- and trans-regulatory elements in TCR-mediated expression of IFN-γ. This study examines CD2 and PMA/ionophore-responsive IFN-γ promoter elements. Activation of LPMC via CD2-induced IFN-γ secretion and a parallel up-regulation of mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Mucosa-specific IFNG response elements have previously been identified within the À204 and À108 bp region. 14 In the present study, we show that an SNP (À179G/T) recently detected within this region 17 exhibits selective allele-specific enhanced expression compared to the common allele in PBMC, but not in LPMC. In PBMC transfected with reporter constructs containing the polymorphic À179T, there is a CD2-mediated doubling of promoter activity compared to the common À179G allele.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Mucosa-specific IFNG response elements have previously been identified within the À204 and À108 bp region. 14 In the present study, we show that an SNP (À179G/T) recently detected within this region 17 exhibits selective allele-specific enhanced expression compared to the common allele in PBMC, but not in LPMC. In PBMC transfected with reporter constructs containing the polymorphic À179T, there is a CD2-mediated doubling of promoter activity compared to the common À179G allele.…”
Section: Discussionsupporting
confidence: 51%
“…[6][7][8] We have previously demonstrated that there are mucosa-specific mechanisms for T-cell cytokine gene regulation of IFN-g expression, which differ from those seen in PBL. 11,[13][14][15]22 Studies by other groups have indicated that regulation of IFN-g gene expression in primary T cells differs from that observed in tumor T-cell lines, and likewise, differs in naïve compared to memory T-cell subsets. [23][24][25] Differential cytokine gene regulation may be controlled, in part, Novel ERE-like cis-element in IFNG promoter R Gonsky et al by DNA methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations